2016
DOI: 10.1186/s13046-016-0341-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A-B55δ enhances chemotherapy sensitivity of human hepatocellular carcinoma under the regulation of microRNA-133b

Abstract: BackgroundHepatocellular carcinoma (HCC) remains a major public health problem worldwide. The identification of effective chemotherapeutic targets for advanced HCC patients is urgently required. In this study, we investigated the role of protein phosphatase 2A-B55δ subunit (PP2A-B55δ, encoded by the PPP2R2D gene) and related mechanisms affecting chemotherapy sensitivity of HCC.MethodsExperimental approaches for measuring the levels of PPP2R2D mRNA and B55δ protein in HCC included bioinformatics analyses, quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
(41 reference statements)
1
44
0
Order By: Relevance
“…In our previous research, protein phosphatase 2A-B55δ subunit enhanced the sensitivity of HCC to cisplatin (cDDP) chemotherapy [54]. In the present study, anti-HBx, the novel mcAb specifically target to the intracellular HBx protein were used.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous research, protein phosphatase 2A-B55δ subunit enhanced the sensitivity of HCC to cisplatin (cDDP) chemotherapy [54]. In the present study, anti-HBx, the novel mcAb specifically target to the intracellular HBx protein were used.…”
Section: Discussionmentioning
confidence: 97%
“…All the recombinant viruses infected HepG2 cells. The detailed protocols were described in our previous study 42 . All the polynucleotides, synthesized by Invitrogen (Shanghai, China), are shown in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…They regulate critical aspects of the oncogenic phenotype through the disruption of protein translation by selective binding and degradation of target mRNAs [ 4 ]. An increasing number of studies have shown that dysregulation of miRNA expression plays an important role in cancer initiation, progression, and prognosis, as well as acquired resistance toanticancer agents [ 5 7 ]. Several miRNAs have been found to participate in the pathogenesis of CRC, including miR-21, miR-451, miR-499-5p, miR-375, and miR-142-5p [ 8 ].…”
Section: Introductionmentioning
confidence: 99%